The Contribution Of Tarekat Qadiriyyah Wa Naqsabandiyyah Berjan To Improving The Work Ethos Of Educational Workers IAI An Nawawi Purworejo - Muhaini, Akhmad; Suwito; Khotimah, Khusnul; Sahimi, Mohd Shafiq (Advances in Humanities and Contemporary Studies, 2024)
There is an assumption that the tarekat makes its followers have a low work ethic and has an impact on poverty. This is because in the tarekat there are teachings that tend to weaken the work ethic, such as the concept of zuhd in the second century hijriyah which tends to be extreme in totally leaving worldly life and the tarekat follower’s habit of reciting dhikr takes up time, thus reducing time in fulfilling worldly life. This research examines the contribution of the Qadiriyyah Wa Naqsabandiyyah Berjan Congregation at IAI An Nawawi Purworejo to the work ethic of educational staff. Study This is included in the field study category and this research is qualitative in nature using a phenomenological approach. Data is collected in three ways, namely observation, interviews, and documentation. The results of the study stated that the work ethic of the Qadiriyyah Wa Naqsabandiyyah Berjan educational staff at IAI An Nawawi Purworejo has increased, the increased work ethic is inseparable from the influence of the teachings, practices and activities of the Qadiriyyah Wa Naqsabandiyyah Berjan Order. The indicators of an increased work ethic are discipline, honesty, responsibility, hard work, optimism and trustworthiness. This research shows that the relation of religion, especially the tarekat to the work ethic, does not result in the followers of the tarekat entering into an understanding of capitalism which tends to have hedonism characteristics. However, the tarekat’s relationship with its work ethic results in its followers being generous, humble and loving one another.